Structure, thermal and microwave dielectric properties of cold-sintered Li2MoO4Al2O3 ceramic - Naichao Chen; Jin Cheng; Xinwei Xu; Hongye Wang; Xiaoyu Li; Zhan Zeng; Bingfeng Zhao; Mingzhao Xu; Hong Wang (Journal of Materiomics, 2025)
Dielectric ceramics are essential components in communication systems that operate within the microwave frequency range. In high-density packages, dielectric substrates ceramics must possess high thermal conductivity to efficiently dissipate heat. However, achieving adequate thermal conductivity (κ) in ceramics sintered at low temperatures is challenging. In this study, we employed the cold sintering process (CSP) to fabricate Li2MoO4-x%Al2O3 (0≤x ≤ 80, in volume) ceramics under 200 MPa pressure at 150 °C. The Li2MoO440%Al2O3 composite exhibited significantly enhanced κ of 5.4 W·m−1·K−1, an 80% increase compared to pure Li2MoO4 ceramic with κ of 3 W·m−1·K−1. At 40% Al2O3 content, the Li2MoO4Al2O3 ceramic demonstrated notable microwave properties (ε ∼ 6.67, Q×f ∼ 17,846 GHz, τf ∼ −105 × 10−6 °C-1). Additionally, simulation of a microstrip patch antenna for 5 GHz applications using Li2MoO420%Al2O3 ceramic as dielectric substrate via Finite Element Simulation software showed excellent performance, with radiation efficiency exceeding 99% and low return loss (S11 < −30 dB) at both 4.9 GHz and 28.0 GHz center frequencies. These findings underscore the suitability of Li2MoO4Al2O3 ceramics for microwave dielectric substrate.